Upaya Guru Bahasa Arab dalam Meningkatkan Kemampuan Membaca Teks Arab dengan Metode Mubasyaroh Kelas V di MI Al Kalam Denpasar Tahun Pelajaran 2019-2020 - Purnomo, Ade; Fawaid, Mohammad; Ismail, Syarof Nursyah (Faidatuna, 2020)
In order to improve the ability to read Arabic texts in elementary school students, the efforts of teachers are needed, especially here, the efforts of Arabic teachers. Because students at the elementary school level still really need guidance in reading and writing Arabic texts. MI Al-Kalam Denpasar Bali is one of the Madrasah Ibtidaiyah in West Denpasar sub-district whichaims to make students ableto read Arabic texts well. Where as in fact the portion of Arabic learning hours in the 2013 curriculum (K13) was only 2 meetings. There for, there search wants try to reveal how the efforts of Arabic teachers in improving the ability to understand Arabic texts at MI Al-Kalam Denpasar Bali. This study aimsto: (1). To find out how the efforts of Arabic teachers in improving the ability to read Arabic text with the mubasyaroh method of grade V students at MI Al-Kalam Denpasar in the 2019/2020 academic year, (2). What are the inhibiting and supporting factors of the mubasyaroh method in learning Arabic in improving the ability to read Arabic text for fifth grade students of MI Al-Kalam Denpasar for the 2019/2020 academic year. The methods used are qualitative methods, research approaches and types, determiningin formants, data collection techniques, data validity, and data analysis techniques. As well as the methods used in data collection techniques, namely: observation, interviews, and documentation. The technique for collecting research informants uses 6 informant consisting of: theprincipal, subject teacher, and class V student guardian.The results of the study revealed that: (1) the efforts made by the Arabic teacher to improve the students' ability to read Arabic texts were being accustomed to repeating mufradat and practicing it everyday. (2) the supporting factor of the application of the mubasyaroh method is that children canget to know more quickly without having to know the writing but directly put into practice. while the inhibiting factor is the lack of students in understanding vocabulary.